Impact of anemia on long-term ischemic events and bleeding events in patients undergoing percutaneous coronary intervention: a system review and meta-analysis - Wang, Xiaoyan; Qiu, Miaohan; Qi, Jing; Li, Jing; Wang, Heyang; Li, Yi; Han, Yaling (Journal of Thoracic Disease; Vol 7, No 11 (November 28, 2015): Journal of Thoracic Disease, 2015)
Background: Data focused on the ischemic events and bleeding events are still limited. We systematically reviewed the current available literature to investigate whether anemia increase incidence of long-term ischemic events and long-term bleeding events in patients undergoing PCI. Methods: PubMed and Embase were searched for case-control studies regarding the impact of anemia on long-term outcomes in patients undergoing percutaneous coronary intervention (PCI). The primary outcome was long-term ischemic events and long-term bleeding events. Mantel-Haenszel method with random effects model or fixed effects model was used to calculate pooled odds ratios (ORs) and 95% confidence intervals (CIs). Results: Seventeen studies involving 68,528 patients (17,123 anemic patients and 51,405 non-anemic patients) were included. Pooled analysis suggested that anemic patients were at higher risk for long-term composite ischemic events (OR: 1.95, 95% CI, 1.21-3.14, P